การปรับผิวผ้าฝ้ายเคลือบไคโตซานด้วยโซเดียมไนไตรต์เพื่อเพิ่มความสามารถในการย้อมสีรีแอกทีฟ - เสรณี ศรีสุข (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
Sodium nitrite was employed for in-situ depolymerization of coated chitosan in order to remove chitosan film from the fabric surface, aiming at solving the problems of surface dyeing and fabric stiffness. Chitosan coated-cotton fabrics were prepared using pad-dry-cure method of which the curing temperature of 150 ◦C for 3 minutes was used. Following that, treatment of coated fabric with sodium nitrite was performed using an exhaustion method at room temperature. The resultant treated fabrics were dyed with a reactive dye and then subjected to testings including dyeability, color strength, stiffness and color fastness properties. The results showed that chitosan coated fabrics exhibited the highest %E value due to the enhancing effect of chitosan amino groups. Whilst, sodium nitrite treated-chitosan fabrics exhibited a relatively lower %E value, albiet more than %E value of untreated fabric, indicating chitosan was partially removed. In comparision, the chitosan coated fabric’s color strength(K/S value which was higher than K/S value of control fabric) was comparable to those of sodium nitrite treated fabric. The improvement in K/S value was due to the availibity of chitosan amino groups which was capable of reacting with reactive dyes. Other fabric properties were evaluated. The results showed that properties of sodium nitrite treated chitosan-coated fabrics including color fastness properties (crocking fastness and wash fastness) and fabric stiffness were found comparable to those of dyed untreated fabric (commercial dyeing). The light fastness of chitosan coated fabrics was poorest. After treatment with sodium nitrite, this property was improved. When considering the percent reduction of fading, this value decreased with an increase in the concentration of sodium nitrite. These finding results led to conclusion that problems of poorer fastness properties and stiffness arising from chitosan coating onto cotton fabric were minimized by sodium nitrite treatment due to the removal of chitosan coated film present on the fabric surface. The remaining chitosan on the fabric surface showed its ability of enhancing reactive dyeability without causing interference to fabric’s fastness properties.